Do Motivation, Compensation, and Work Environment Improve Employee Performance: A Literature Review - Nur’aeni Nur’aeni; Abu Muna Almaududi Ausat; Yudiyanto Joko Purnomo; Abdul Razak Munir; Suherlan Suherlan (International Journal of Artificial Intelligence Research, 2022)
Every employee wants to succeed, thus many are loyal. Some company loyalists seek justice. Businesses must encourage employee performance to succeed. Motivation, compensation, and work environment affect employee performance. This study analyzes and provides evidence that motivation, compensation, and work environment improve employee performance. This literature review article develops a conceptual framework on employee performance based on motivation, compensation, and work environment theories. According to the literature review, motivation, compensation, and work environment can boost employee performance and corporate performance. This study supports Abraham Maslow's theory (The Need Hierarchy Model) that motivation substantially influences human behavior. Motivation directs persons to their needs. A leader must know his subordinates' requirements. This study's research model and arguments can advance corporate or business management and administration discussions. This research is relevant for future quantitative, qualitative, and mixed-methods research.